LINC01410 promotes cell proliferation and migration of cholangiocarcinoma through modulating miR‐124‐3p/SMAD5 axis. (7th April 2020) - Jiang, Tao; Wang, Chunlin; Zhu, Yunxie; Han, Huaxin
Abstract: Background: Cholangiocarcinoma (CCA) is generally associated with high incidence and poor prognosis. Nowadays, increasing experimental data demonstrate that long non‐coding RNA (lncRNA) plays an indispensable role in tumor occurrence. Nevertheless, the specific mechanism of lncRNA is not clear in CCA. Methods: The relative expressions of lncRNAs, miRNAs, and mRNAs were detected by real‐time quantitative PCR (RT‐qPCR). CCK8 and colony formation assays were applied to examine cell proliferation ability in CCA. Transwell assay was conducted to measure the migration and invasion capabilities of CCA cells. Nuclear and cytoplasmic separation assay was implemented to figure out the location of LINC01410. Luciferase reporter assay, RIP and RNA pull‐down assays were applied to certify the molecular bindings. Western blot was applied to detect the protein level. Results: The high expression of LINC01410 was proved in CCA tissues and CCA cell lines. Also, CCA patients with high LINC01410 level presented poor prognosis. LINC01410 deficiency impeded cell proliferation, migration and invasion in HuCCT1 and RBE cell lines. What's more, LINC01410 interacted with miR‐124‐3p. Meanwhile, SMAD5 targeted and inhibited by miR‐124‐3p. SMAD5 expression was enhanced by LINC01410. Conclusion: LINC01410 facilitates cell proliferation, migration and invasion through miR‐124‐3p/SMAD5 axis.